WNK1 promotes renal tumor progression by activating TRPC6‐NFAT pathway. Issue 7 (25th April 2019) - Kim, Ji‐Hee; Hwang, Kyu‐Hee; Eom, Minseob; Kim, Minseon; Park, Eun Young; Jeong, Yangsik; Park, Kyu‐Sang; Cha, Seung‐Kuy
ABSTRACT: Deregulation of Ca 2+ signaling has been regarded as one of the key features of cancer progression. Lysine‐deficient protein kinase 1 (WNK1), a major regulator of renal ion transport, regulates Ca 2+ signaling through stimulating the phosphatidylinositol 4‐kinase IIIα (PI4KIIIα) to activate Gαq‐coupled receptor/PLC‐β signaling. However, the contribution of WNK1‐mediated Ca 2+ signaling in the development of clear‐cell renal‐cell carcinoma (ccRCC) is yet unknown. We found that the canonical transient receptor potential channel (TRPC)6 was widely expressed in ccRCC tissues and functioned as a primary Ca 2+ influx mechanism. We further identified that the expressions of WNK1, PI4KIIIcα, TRPC6, and the nuclear factor of activated T cells cytoplasmic 1 (NFATc1) were elevated in the tumor tissues compared with the adjacent normal tissues. WNK1 expression was directly associated with the nuclear grade of ccRCC tissues. Functional experiments showed that WNK1 activated TRPC6‐mediated Ca 2+ influx and current by stimulating PI4KIIIα. Notably, the inhibition of WNK1‐mediated TRPC6 activation and its downstream substrate calcineurin attenuated NFATc1 activation and the subsequent migration and proliferation of ccRCC. These findings revealed a novel perspective of WNK1 signaling in targeting the TRPC6‐NFATc1 pathway as a therapeutic potential for renal‐cell carcinoma.—Kim, J.‐H., Hwang, K.‐H., Eom, M., Kim, M., Park, E. Y., Jeong, Y., Park, K.‐S., Cha, S.‐K. WNK1 promotes renal tumor progression by activating TRPC6‐NFAT pathway. FASEB J. 33, 8588–8599 (2019). www.fasebj.org